Composite material and method for manufacturing composite material structure
By using surface-modified composite technology of MXene and specific cationic resin materials, the problem of performance degradation of traditional composite materials in high humidity environments is solved, achieving higher humidity resistance and long-term stability.
Patent Information
- Application Number
- JP2023578410
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-02-02
- Filing Date
- 2022-12-16
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2042-12-16
AI Technical Summary
The traditional composite of MXene and resin materials exhibits lower environmental resistance, especially humidity resistance, in high humidity environments, resulting in changes in physical properties over time, especially reduced conductivity.
The composite material containing a two-dimensional material (MXene) with a specific surface modification and a cationic resin material with hydroxy acid groups or other specific functional groups is used to improve the environmental resistance of the composite material by adjusting the type and proportion of the resin material.
The humidity resistance and long-term stability of the composite material are significantly improved, ensuring that its conductive properties are maintained even better than MXene materials alone.
Smart Images

Figure 0007670178000004 
Figure 0007670178000005 
Figure 0007670178000006
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a composite material, more particularly to a composite material containing inorganic particles and a resin material, and a method for producing a composite material structure. [Background technology]
[0002] In recent years, MXene has been attracting attention as a new material having electrical conductivity. MXene is a type of so-called two-dimensional material, and more specifically, as described below, it is a two-dimensional material (layered material) having the form of one or more layers. In general, MXene has the form of particles (which may include powder, flakes, nanosheets, etc.) of such two-dimensional materials (layered materials).
[0003] Conventionally, composite materials of MXene and resin materials (polymer materials) have been known. For example, Non-Patent Document 1 describes a composite material in which MXene is filled into polyurethane by applying an emulsion method. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Weiqiang Zhi, et al., "Study of MXene-filled polyurethane nanocomposites prepared via an emulsion method", Composites Science and Technology, 2018, vol.168, pp.404-411 Summary of the Invention [Problem to be solved by the invention]
[0005] It is known that the physical properties of objects made of MXene alone (such as films) change over time (typically, the electrical conductivity decreases over time). This is thought to be due to the moisture absorption of MXene.
[0006] Research by the present inventors has revealed that when an object is constructed from a composite material (hereinafter simply referred to as a "conventional composite material") containing MXene and a resin material conventionally used in the relevant technical field (such as polyurethane, see Non-Patent Document 1), the physical properties of the object constructed from the conventional composite material change more significantly over time (typically, the electrical conductivity decreases more significantly over time) compared to an object constructed from only MXene (MXene simple material). This tendency is more pronounced in high humidity environments (e.g., relative humidity of 85%). In other words, research by the present inventors has revealed that the above-mentioned conventional composite material containing MXene and a resin material (such as polyurethane) has a problem of lower environmental resistance (particularly moisture resistance) than MXene simple material.
[0007] An object of the present disclosure is to provide a novel composite material containing MXene and a resin material, which has improved environmental resistance (particularly moisture resistance) compared to conventional composite materials. A further object of the present disclosure is to provide a novel method for producing a composite material structure containing MXene and a resin material. [Means for solving the problem]
[0008] [1] 1. A composite material comprising particles of a two-dimensional material comprising one or more layers and a resin material, The layer comprises a compound having the following formula: M m X n (wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 or more and 4 or less, m is greater than n and less than or equal to 5) and a modification or termination T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, The composite material is an anionic resin material (excluding a resin material containing polyvinyl alcohol) containing an anionic polymer having at least one of a carboxylic acid group and a carboxylate salt group and having no NH group.
[0009] [2] The composite material according to the above [1], having the form of a structure.
[0010] [3] The composite material according to [2] above, wherein the structure is a membrane.
[0011] [4] The composite material according to any one of the above [1] to [3], wherein the resin material is an acrylic resin material.
[0012] [5] The composite material according to any one of the above [1] to [4], wherein the resin material is a self-crosslinking resin material.
[0013] [6] The composite material according to any one of [1] to [5] above, wherein the ratio of the solid content of the resin material to the total of the two-dimensional material particles and the solid content of the resin material in the composite material is 0.1 mass% or more and 99.9 mass% or less.
[0014] [7] Said M m X n is Ti3C2.
[0015] [8] 1. A method for manufacturing a composite material structure, comprising the steps of: (a) preparing a liquid composition comprising particles of a two-dimensional material comprising one or more layers, a resin material, and a liquid medium, The layer comprises a compound having the following formula: M m X n (wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 or more and 4 or less, m is greater than n and less than or equal to 5) and a modification or termination T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, The resin material is an anionic resin material containing an anionic polymer having at least one of a carboxylic acid group and a carboxylate salt group and having no NH group (excluding resin materials containing polyvinyl alcohol); and (b) forming a precursor structure on a substrate using the liquid composition, and at least drying the precursor structure to obtain a composite material structure; A manufacturing method comprising:
[0016] [9] The method for producing a composite material structure according to [8] above, wherein the composite material structure is a composite material membrane.
[0017]
[10] The method for producing a composite material structure according to the above [8] or [9], wherein the resin material is an acrylic resin material.
[0018]
[11] The method for producing a composite material structure according to any one of the above [8] to
[10] , wherein in the step (a), the resin material is a self-crosslinking resin material.
[0019]
[12] The method for producing a composite material structure according to any one of [8] to
[11] above, wherein in (a), the ratio of the solid content of the resin material in the liquid composition to the total of the particles of the two-dimensional material and the solid content of the resin material is 0.1 mass% or more and 99.9 mass% or less.
[0020]
[13] Prior to (a) above, The following formula: M m AXn (In the formula, M, X, n, and m are as defined above, A is at least one Group 12, 13, 14, 15, or 16 element. and obtaining particles of the two-dimensional material by a method comprising the steps of: etching a raw material represented by the formula: with an etching solution containing hydrofluoric acid. The method for producing a composite material structure according to any one of the above [8] to
[12] , further comprising:
[0021]
[14] Prior to (a) above, The following formula: M m AX n (In the formula, M, X, n, and m are as defined above, A is at least one Group 12, 13, 14, 15, or 16 element. Obtaining particles of said two-dimensional material by a method comprising etching a raw material represented by the formula: with an etching solution containing a fluoride and an acid (but excluding hydrofluoric acid). The method for producing a composite material structure according to any one of the above [8] to
[12] , further comprising:
[0022]
[15] The method for producing a composite material structure according to any one of the above [8] to
[14] , wherein in (b), the precursor structure is formed by spraying the liquid composition onto the substrate.
[0023]
[16] Said M m X n is Ti3C2. Effect of the Invention
[0024] According to the present disclosure, a composite material containing particles of a predetermined two-dimensional material (also referred to as "MXene" in this specification) and a resin material uses an anionic resin material (excluding resin materials containing polyvinyl alcohol) containing an anionic polymer having at least one of a carboxylic acid group and a carboxylate salt group and no NH group, thereby providing a composite material with improved environmental resistance (particularly moisture resistance) compared to conventional composite materials. Also, according to the present disclosure, a novel method for producing a composite material structure containing MXene and the above-mentioned resin material is provided. [Brief description of the drawings]
[0025] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a composite material according to one embodiment of the present disclosure. [Diagram 2] 1A-1B are schematic cross-sectional views showing particles of a two-dimensional material (MXene) that can be used in one embodiment of the present disclosure, where (a) shows a single-layer MXene particle and (b) shows a multi-layer (exemplarily two-layer) MXene particle. [Diagram 3] 1 is a graph showing the change over time in electrical conductivity of the films produced in Example 1 and Comparative Examples 1 and 2. [Figure 4] 1 is a graph showing the change over time in electrical conductivity of the films produced in Example 2 and Comparative Examples 3 and 4. [Diagram 5] 1 is a graph showing the change over time in electrical conductivity of the films produced in Example 3 and Comparative Examples 5 and 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Hereinafter, a method for producing a composite material and a composite material structure (for example, a composite material in the form of a film) in one embodiment of the present disclosure will be described in detail, but the present disclosure is not limited to this embodiment.
[0027] 1, the composite material 20 of this embodiment includes particles 10 of a predetermined two-dimensional material (layered material) and an anionic resin material (excluding resin materials containing polyvinyl alcohol) 11 that includes an anionic polymer having at least one of a carboxylic acid group and a carboxylate group and no NH group (hereinafter, an anionic resin material having such a limitation is also simply referred to as an "anionic resin material") 11. By using such an anionic resin material 11 in combination with the particles 10 of the predetermined two-dimensional material (layered material), it is possible to improve environmental resistance (particularly moisture resistance) compared to conventional composite materials using polyurethane or the like.
[0028] The composite material 20 of this embodiment may have any suitable structure and / or form. For example, the composite material 20 of this embodiment may be a solid or non-fluid structure (substantially free of a liquid medium). The composite material structure may be one that has been molded or formed into a predetermined shape. An example of such a composite material structure is a composite material 20 having a membrane form, in other words, a composite material membrane (shown as the composite material 20 in FIG. 1). However, the composite material 20 of this embodiment is not limited thereto, and may be, for example, a liquid composition (e.g., a slurry, a paste, etc.) further containing a liquid medium (not shown in FIG. 1) described later.
[0029] Hereinafter, the composite material 20 of this embodiment will be described in detail through a method for producing a composite material structure (for example, a composite material membrane). Unless otherwise specified, the explanation of the method for producing a composite material structure can also be applied to the composite material.
[0030] The method for producing a composite material structure according to the present embodiment includes the steps of: (a) preparing a liquid composition comprising particles of a given two-dimensional material (layered material), an anionic resin material, and a liquid medium; and (b) forming a precursor structure on a substrate using the liquid composition, and at least drying the precursor structure to obtain a composite material structure; Includes.
[0031] ·Process (a) <MXene particles> First, prepare particles of a predetermined two-dimensional material (layered material). The predetermined two-dimensional material that can be used in this embodiment is MXene, which is defined as follows: A two-dimensional material (layered material) including one or more layers, where the layer has the following formula: M m X n (In the formula, M is at least one metal of Groups 3, 4, 5, 6, and 7, so-called early transition metals, and may include at least one selected from the group consisting of Sc, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, and Mn. X is a carbon atom, a nitrogen atom, or a combination thereof. n is 1 or more and 4 or less. m is greater than n and 5 or less.) It includes a layer main body represented by (the layer main body may have a crystal lattice in which each X is located within the octahedral array of M), and a modification or termination T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer main body (more specifically, at least one of the two surfaces of the layer main body facing each other). This two-dimensional material can be understood as a layered compound, and is also represented as "M m X n T s ", where s is an arbitrary number, and conventionally, x may be used instead of s). Typically, n can be 1, 2, 3, or 4, but is not limited thereto.
[0032] In the above formula of MXene, M is preferably at least one selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, and Mn, and more preferably at least one selected from the group consisting of Ti, V, Cr, and Mo.
[0033] MXene has the above formula: M m X n which is known to be expressed as follows. Sc2C, Ti2C, Ti2N, Zr2C, Zr2N, Hf2C, Hf2N, V2C, V2N, Nb2C, Ta2C, Cr2C, Cr2N, Mo2C, Mo 1.3 C, Cr 1.3 C, (Ti,V)2C, (Ti,Nb)2C, W2C, W 1.3 C, Mo2N, Nb 1.3 C, Mo 1.3 Y 0.6 C (in the above formula, "1.3" and "0.6" mean approximately 1.3 (= 4 / 3) and approximately 0.6 (= 2 / 3), respectively), Ti3C2, Ti3N2, Ti3(CN), Zr3C2, (Ti,V)3C2, (Ti2Nb)C2, (Ti2Ta)C2, (Ti2Mn)C2, Hf3C2, (Hf2V)C2, (Hf2Mn)C2, (V2Ti)C2, (Cr2Ti)C2, (Cr2V)C 2, (Cr2Nb)C2, (Cr2Ta)C2, (Mo2Sc)C2, (Mo2Ti)C2, (Mo2Zr)C2, (Mo2Hf)C2, (Mo2V)C2, (Mo2Nb)C2, (Mo2Ta)C2, (W2Ti)C2, (W2Zr)C2, (W2Hf)C2, Ti4N3, V4C3, Nb4C3, Ta4C3, (Ti,Nb)4C3, (Nb,Zr)4C3, (Ti2Nb2)C3, (Ti2Ta2)C3, (V2Ti2)C3, (V2Nb2)C3, (V2Ta2)C3, (Nb2Ta2)C3, (Cr2Ti2)C3, (Cr2V 2)C3, (Cr2Nb2)C3, (Cr2Ta2)C3, (Mo2Ti2)C3, (Mo2Zr2)C3, (Mo2Hf2)C3, (Mo2V2)C3, (Mo2Nb2)C3, (Mo2Ta2)C3, (W2Ti2)C3, (W2Zr2)C3, (W2Hf2)C3, (Mo 2.7 V 1.3 ) C3 (In the above formula, "2.7" and "1.3" mean approximately 2.7 (= 8 / 3) and approximately 1.3 (= 4 / 3), respectively.)
[0034] Representatively, M m X n However, Ti2C, Ti3C2, Ti3(CN), (Cr2Ti)C2, (Mo2Ti)C2, (Mo2Ti2)C3, and (Mo 2.7 V 1.3) C3.
[0035] In particular, M m X n may be Ti3C2.
[0036] Such MXene particles (hereinafter simply referred to as "MXene particles") can be synthesized by selectively etching (removing and optionally separating) A atoms (and optionally some M atoms) from the raw material MAX phase.
[0037] In other words, the manufacturing method for the composite material structure of this embodiment may further include a step of obtaining MXene particles prior to step (a), and the step of obtaining MXene particles includes etching the raw material MAX phase with an etching solution (etching treatment).
[0038] The raw material MAX phase (hereinafter also simply referred to as "MAX raw material") has the following formula: M m AX n (wherein M, X, n and m are as defined above, and A is at least one Group 12, 13, 14, 15, 16 element, usually a Group A element, typically Group IIIA and Group IVA, and more particularly may include at least one element selected from the group consisting of Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, As, S and Cd, and is preferably Al). The MAX phase is represented by M m X n (each X may have a crystal lattice in which it is located in the octahedral array of M) between which a layer composed of A atoms is located. In the MAX phase, typically when m=n+1, one layer of X atoms is arranged between each of the n+1 layers of M atoms (collectively referred to as "M m X nThe MAX phase has a repeating unit in which a layer of A atoms (also referred to as an "A layer") is arranged as a layer next to the n+1th layer of M atoms, but is not limited thereto. The A atoms (and sometimes a part of the M atoms) are selectively etched (removed and sometimes layer separated) from the MAX phase, thereby removing the A atom layer (and sometimes a part of the M atoms) to expose the M m X n The surface of the layer is modified with hydroxyl groups, fluorine atoms, chlorine atoms, oxygen atoms, hydrogen atoms, etc. present in the etching solution (usually, an aqueous solution containing hydrofluoric acid is used, but is not limited to this) to terminate the surface.
[0039] The etchant may include any suitable acid (HF, HCl, HBr, HI, sulfuric acid, phosphoric acid, nitric acid, etc.).
[0040] For example, the MAX raw material may be etched with an etching solution containing hydrofluoric acid. By using hydrofluoric acid as the etching solution, hydrofluoric acid (HF) is present in the etching solution. The etching process using an etching solution containing hydrofluoric acid may also be called an ACID method. In addition to hydrofluoric acid, the etching solution may further contain other acids such as hydrochloric acid, hydrobromic acid, hydroiodic acid, nitric acid, sulfuric acid, acetic acid, formic acid, hypochlorous acid, and fluorosulfonic acid.
[0041] Alternatively, for example, the MAX raw material may be etched with an etching solution containing fluoride and acid (except hydrofluoric acid). By using fluoride and acid (except hydrofluoric acid) in the etching solution, hydrofluoric acid (HF) is present in situ in the etching solution. The etching process using an etching solution containing fluoride and acid (except hydrofluoric acid) may also be referred to as the MILD method. As the fluoride, a metal fluoride such as lithium fluoride, sodium fluoride, potassium fluoride, etc. may be used, and may be lithium fluoride in particular. When a metal fluoride is used, in the etching process, a metal (metal ion) may be intercalated into the MXene particles along with the etching of the MAX raw material. As the acid (except hydrofluoric acid), for example, hydrochloric acid, hydrobromic acid, hydroiodic acid, nitric acid, sulfuric acid, acetic acid, formic acid, hypochlorous acid, fluorosulfonic acid, etc. may be used, and may be hydrochloric acid in particular. As the fluoride and acid (except for hydrofluoric acid), ammonium hydrogen difluoride may be used.
[0042] In this embodiment, etching using an etching solution containing hydrofluoric acid (ACID method) is preferable to etching using an etching solution containing fluoride and acid (excluding hydrofluoric acid) (MILD method) (see the examples described later).
[0043] The process of obtaining MXene particles may include any suitable treatment after the etching treatment, as appropriate. Such treatments include, for example, washing, intercalation, delamination, etc. Washing may be performed by applying a water wash, followed by centrifugation / decantation. Intercalation may involve intercalating a metal (metal ion) into the MXene particles. Delamination may involve applying an impact, such as vibration and / or ultrasound, to promote delamination of the MXene particles (converting multi-layered MXene particles into MXene particles with fewer layers, e.g., single-layered MXene particles). For example, the delamination treatment may be performed for a predetermined time by hand shaking, an automatic shaker, a mechanical shaker, a vortex mixer, a homogenizer, an ultrasonic bath, etc.
[0044] In the present disclosure, the MXene particles may contain a relatively small amount of residual A atoms, for example, 10% by mass or less of the original A atoms. The amount of residual A atoms may be preferably 8% by mass or less, more preferably 6% by mass or less. However, even if the amount of residual A atoms exceeds 10% by mass, there may be cases where this does not pose a problem depending on the application and use conditions of the composite material.
[0045] The MXene particles 10 thus synthesized may be particles of layered material comprising one or more MXene layers 7a, 7b, as shown diagrammatically in FIG. 2 (non-limiting examples of MXene particles 10 include a single layer MXene particle 10a shown in FIG. 2(a) and a two layer MXene particle 10b shown in FIG. 2(b)). More specifically, the MXene layers 7a, 7b may be made of M m X n The layer body (M m X n The MXene layers 7a, 7b have "M m X n T s ", where s is any number. The MXene particles 10 may be those in which the MXene layers are individually separated and present as one layer (single layer structure shown in FIG. 2(a), so-called single layer MXene particles 10a), or may be a laminate in which a plurality of MXene layers are stacked at a distance from one another (multilayer structure shown in FIG. 2(b), so-called multilayer MXene particles 10b), or a mixture thereof. The MXene particles 10 may be particles (which may also be referred to as powder or flakes) as an aggregate composed of single layer MXene particles 10a and / or multilayer MXene particles 10b. In the case of multilayer MXene particles, two adjacent MXene layers (e.g. 7a and 7b) do not necessarily have to be completely separated, and may be partially in contact.
[0046] Without being limiting to this embodiment, the thickness of each MXene layer (corresponding to the above-mentioned MXene layers 7a and 7b) is, for example, 0.8 nm or more and 5 nm or less, particularly 0.8 nm or more and 3 nm or less (which may vary mainly depending on the number of M atomic layers contained in each layer), and the maximum dimension in a plane parallel to the layer (two-dimensional sheet surface) (which may correspond to the "in-plane dimension" of the particle) is, for example, 0.1 μm or more, particularly 1 μm or more, for example 200 μm or less, particularly 40 μm or less.
[0047] When the MXene particles are laminate (multilayer MXene) particles, the interlayer distance (or gap dimension, shown as Δd in Figure 2(b)) within each laminate particle is not particularly limited, and is, for example, 0.8 nm or more and less than 10 nm, particularly 0.8 nm or more and 5 nm or less, more particularly about 1 nm, and the maximum dimension in a plane perpendicular to the stacking direction (two-dimensional sheet surface) (which may correspond to the ``in-plane dimension'' of the particle) is, for example, 0.1 μm or more, particularly 1 μm or more, for example 100 μm or less, particularly 20 μm or less.
[0048] The total number of layers in the MXene particle may be 1 or 2 or more, for example, 1 to 20, and the thickness in the stacking direction (which may correspond to the "thickness" of the particle) is, for example, 0.8 to 20 nm.
[0049] When the MXene particles are laminate (multilayer MXene) particles, they may be MXenes with a small number of layers. The term "small number of layers" refers to, for example, MXenes with six or fewer stacked layers. The thickness of the multilayer MXenes with a small number of layers in the stacking direction may be less than 10 nm. In this specification, this "multilayer MXene with a small number of layers" is also referred to as "few-layer MXenes."
[0050] Although not limiting this embodiment, the MXene particles may be particles (which may also be referred to as nanosheets) composed mostly of monolayer MXene and / or few-layer MXene. In this specification, monolayer MXene and few-layer MXene may be collectively referred to as "monolayer / few-layer MXene".
[0051] Each of the above dimensions can be determined as a number average dimension (e.g., number average of at least 40) based on photographs taken with a scanning electron microscope (SEM), a transmission electron microscope (TEM), or an atomic force microscope (AFM), or as a distance in real space calculated from the position in reciprocal space of the (002) plane measured by X-ray diffraction (XRD).
[0052] <Anionic resin materials> Separately, an anionic resin material is prepared. In the present disclosure, the "anionic resin material" refers to an anionic resin material that contains an anionic polymer having at least one of a carboxylic acid group and a carboxylate salt group and no NH group (however, resin materials containing polyvinyl alcohol are excluded).
[0053] An anionic polymer is a polymer (high molecular weight polymer) that has an anionic functional group and exhibits a negative charge (a negative zeta potential) in a liquid medium. The ratio of monomer units having an anionic functional group in the anionic polymer is not particularly limited as long as the anionic polymer exhibits a negative charge (a negative zeta potential) in a liquid medium. The anionic resin material may contain an anionic polymer. The anionic resin material may contain any other appropriate component in addition to the anionic polymer. The anionic resin material may contain one or more anionic polymers, but preferably does not contain a high molecular weight polymer other than the anionic polymer.
[0054] The anionic polymer having at least one of a carboxylic acid group and a carboxylate salt group means that it has -COOH and / or -COOX' (X' is a monovalent ion such as sodium, potassium, ammonium, etc.). The carboxylic acid group and the carboxylate salt group are represented by -COO - The anionic polymer may or may not further contain at least one other anionic functional group, such as a sulfonic acid group, a sulfonate group, a phosphoric acid group, and a phosphoric acid group.
[0055] In the present disclosure, the anionic polymer must not have an NH group. The NH group may be -N(H)- present in the main chain and / or side chain of the polymer, and the H of the NH group may form a hydrogen bond. Thus, the anionic polymer does not have, for example, a urethane bond (-NHCOO-).
[0056] However, the anionic resin material usable in the present disclosure excludes a resin material containing polyvinyl alcohol (PVA) (hereinafter, also simply referred to as a "PVA-containing resin material"). The PVA-containing resin material excluded in the present disclosure is a resin material containing PVA in addition to an anionic polymer. PVA (polyvinyl alcohol) means a polymer containing a monomer unit derived from vinyl alcohol as a main component. PVA can be, for example, a homopolymer of vinyl alcohol or a copolymer of vinyl alcohol and vinyl acetate. PVA can be understood as a nonionic polymer with a hydroxyl group as a nonionic functional group. In other words, the PVA-containing resin material excluded in the present disclosure can be understood as an anionic-nonionic hybrid resin material since it contains an anionic polymer and PVA, which is a nonionic polymer. In addition, hydroxyl groups, alkylene oxide groups, etc. are known as examples of nonionic functional groups.
[0057] In this embodiment, the anionic resin material may be an acrylic resin material. In other words, the anionic resin material may contain an anionic acrylic polymer as an anionic polymer. Such an anionic acrylic polymer has at least one of a carboxylic acid group and a carboxylate group, and does not have an NH group. The acrylic polymer means a polymer containing a monomer unit derived from a (meth)acryloyl group as a main component. The "(meth)acryloyl group" means an acryloyl group and / or a methacryloyl group. The main component means a component that occupies 50% by mass or more of the polymer.
[0058] In this embodiment, the anionic resin material is preferably a self-crosslinking resin material. The self-crosslinking anionic resin material may be an anionic polymer (e.g., an anionic acrylic polymer) having a self-crosslinking functional group introduced therein, which can be crosslinked by the anionic polymer alone, or an anionic polymer having a reactive functional group introduced therein, which can be crosslinked by reacting with a crosslinking agent, or both of these.
[0059] For example, crosslinking may be performed by a crosslinking reaction between a polymer having a reactive functional group such as a carboxylic acid group, a sulfonic acid group, a carbonyl group, or a hydroxyl group introduced therein and a crosslinking agent having a crosslinkable functional group. And / or crosslinking can also be performed by copolymerizing a crosslinkable monomer having two or more vinyl groups in one molecule (e.g., ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, divinylbenzene, etc.), or by introducing a monomer having a self-crosslinkable functional group (e.g., a methylol group-containing monomer, a hydrolyzable silyl group-containing monomer, etc.).
[0060] Other components that may be included in the anionic resin material may be additives. Examples of additives include, but are not limited to, surfactants, curing agents and / or crosslinking agents, viscosity modifiers (e.g., thickeners), etc. Examples of surfactants include tetraethylene glycol, etc.
[0061] Examples of commercially available anionic resin materials include Aron (registered trademark) NW-400 (manufactured by Toagosei Co., Ltd., self-crosslinking type, containing an anionic acrylic polymer having at least one of a carboxylic acid group and a carboxylate group and not having an NH group, containing tetraethylene glycol as a surfactant, and not containing PVA), Lipidure (registered trademark)-A (manufactured by NOF Corporation), etc. In addition, commercially available anionic resin materials as raw materials may further contain a liquid medium as appropriate. In the present disclosure, examples of PVA-containing resin materials excluded from the anionic resin materials include Aron (registered trademark) AS-2000 (manufactured by Toagosei Co., Ltd., non-reactive type, containing an anionic acrylic (acrylic acid-based) polymer and PVA), etc.
[0062] <Liquid Composition> A liquid composition is prepared containing the MXene particles and anionic resin material prepared above in a liquid medium.
[0063] The liquid medium may be either an aqueous medium or an organic medium, but an aqueous medium is preferred. The aqueous medium is typically water, and may contain a relatively small amount of other liquid substances in addition to water (for example, 30% by mass or less, preferably 20% by mass or less based on the total aqueous medium). The organic medium is not particularly limited, but may be, for example, a protic solvent such as alcohol, or an aprotic solvent, or a mixed solvent of two or more of them.
[0064] In the resulting liquid composition, the anionic resin material allows the MXene particles to be well dispersed in the liquid medium. As described below, by using a liquid composition that allows good dispersion of the MXene particles, the environmental resistance (particularly moisture resistance) of the final composite material (which is a composite material structure in this production example, but is not limited to this) can be improved (compared to conventional composite materials).
[0065] The ratio of the solid content of the anionic resin material to the total solid content of the MXene particles and the anionic resin material in the liquid composition may be 0.1% by mass or more and 99.9% by mass or less, and within this range, the effect of improving environmental resistance (particularly moisture resistance) can be achieved. The above ratio in the liquid composition can be substantially the same as the ratio of the solid content of the anionic resin material to the total solid content of the MXene particles and the anionic resin material in the finally obtained composite material (which is a composite material structure in this production example, but is not limited to this).
[0066] The liquid composition may be in the form of a slurry, a paste, or the like, depending on the total solids concentration including the MXene particles and the solids of the anionic resin material, and the like.
[0067] ·Process (b) <Precursor structure> Then, a precursor structure is formed on a substrate using the liquid composition prepared above, and the precursor structure is at least dried to obtain a composite material structure. When the composite material structure is a composite material film, the precursor structure is a precursor film.
[0068] The substrate is not particularly limited, and may be made of any suitable material and may have any suitable structure and / or form. The region of the substrate surface where the precursor structure is formed may be flat or not flat, and may have a surface shape such as a curved surface, an uneven surface, or an irregular shape. The substrate may be, but is not limited to, a substrate, a film, or the like.
[0069] In order to obtain higher adhesion between the finally formed composite material film and the substrate, it is preferable that the substrate surface (the surface on which the precursor structure is formed) has a functional group (e.g., OH group) capable of hydrogen bonding with the MXene particles. Such a functional group may be one that the substrate originally has, or one that is developed by carrying out a pretreatment (e.g., plasma treatment). The pretreatment may be carried out for the purpose of cleaning, hydrophilization, etc.
[0070] The method for forming the precursor structure on the substrate is not particularly limited, and for example, the precursor structure may be formed by spraying the liquid composition on the substrate. However, a method other than spraying, for example, a porous member (e.g., a membrane filter) may be used as the substrate, and the liquid composition may be passed through the porous member (filtered) to form the precursor structure on the porous member. Spraying can orient MXene particles on the substrate (align the two-dimensional sheet surface of the MXene particles so that it is approximately parallel (e.g., within ±20°) to the surface of the substrate), and the composite material structure finally obtained can be made denser than a filtration membrane, and therefore higher environmental resistance (moisture resistance) can be obtained. In addition, any method such as bar coating, spin coating, and immersion can be applied.
[0071] The precursor structure is dried to remove the unwanted liquid medium (not all of the liquid medium is necessarily removed, some may remain) and form a composite structure. The spraying and drying may be repeated to obtain a composite structure of a desired thickness.
[0072] When a self-crosslinking anionic resin material is used, a crosslinking reaction may proceed during the formation of the composite structure. For example, the crosslinking reaction may proceed by at least partially removing the liquid medium by drying. Also, for example, depending on the self-crosslinking anionic resin material used, the crosslinking reaction may proceed by heating, irradiating with radiation (light, ultraviolet light, etc.) under appropriate conditions in addition to drying.
[0073] <Composite material structure> The composite material structure obtained in the above manner is made using a liquid composition that has good dispersibility of MXene particles, and therefore has improved environmental resistance (especially moisture resistance) (compared to films made of conventional composite materials).
[0074] Although the present disclosure is not bound by any theory, the reason why the use of a liquid composition with good dispersibility of MXene particles can improve the environmental resistance (particularly moisture resistance) of the final composite material (which is a composite material structure in this manufacturing example, but is not limited to this) (compared to conventional composite materials) is believed to be as follows.
[0075] MXene particles are M m X n The surface of the layer body represented by the formula (I) has a modification or a terminal T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom), and this structure results in the presence of a charged site. The two-dimensional sheet surface (a plane parallel to the layer of MXene particles) that occupies most of the surface of the MXene particle is usually negatively charged. When the MXene particles are mixed with a liquid medium (typically water), the MXene particles may attract each other in the liquid medium by intermolecular forces or hydrogen bonding forces, and may aggregate. In this embodiment, in addition to the MXene particles and the liquid medium, an anionic resin material is used that contains an anionic polymer that has at least one of a carboxylic acid group and a carboxylate group, and does not have an NH group. The carboxylic acid group and / or the carboxylate group of the anionic polymer are represented by the formula -C(=O)O in the liquid medium. - In addition, =O in the carboxylic acid group and / or carboxylate salt group of the anionic polymer can function as a hydrogen acceptor, and H in the carboxylic acid group of the anionic polymer can function as a hydrogen donor for hydrogen bonding, forming (relatively loose) hydrogen bonds with the MXene particle. Among the modified or terminal T of the MXene particle, fluorine atoms, chlorine atoms, and oxygen atoms can function as hydrogen acceptors, and hydroxyl groups and hydrogen atoms can function as hydrogen donors. Thus, in a liquid medium, the negative charge on the surface of the MXene particle and the -C(=O)O of the anionic polymer can function as hydrogen acceptors for hydrogen bonding. -While there is strong electrostatic repulsion between the MXene particles and the anionic polymer, loose hydrogen bonds can be formed between the MXene particles and the anionic polymer (note that the anionic polymer contains multiple monomer units having carboxylic acid groups and / or carboxylate salt groups). Such electrostatic repulsion and hydrogen bonds are well balanced, and as a result, aggregation between the MXene particles is effectively prevented by the steric repulsion of the anionic polymer, allowing the MXene particles to be well dispersed. MXene particles are extremely sensitive to the functional groups of the polymer, and the MXene particles can be well dispersed by using an anionic polymer having carboxylic acid groups and / or carboxylate salt groups, which are anionic and electrostatically repulsive, among the anionic functional groups, and which can form loose hydrogen bonds.
[0076] Such good dispersibility of the MXene particles can be ensured by the anionic polymer having no NH group. The NH group can function as a cationic functional group. The NH group can also function as a hydrogen donor, and the MXene particles can form strong hydrogen bonds with the NH group. If the anionic polymer has an NH group, in a liquid medium, electrostatic attraction acts between the negative charge on the surface of the MXene particles and the NH group of the anionic polymer, or hydrogen bonds between the MXene particles and the NH group of the anionic polymer are too strong, and the MXene particles are connected to each other via the anionic polymer, which can cause aggregation of the MXene particles. In this embodiment, since the anionic polymer does not have an NH group, such problems can be avoided.
[0077] In addition, the anionic resin material usable in the present disclosure is one other than a PVA-containing resin material. The inventors have confirmed that PVA has an extremely strong effect of aggregating MXene particles. Even if a PVA-containing resin material contains an anionic polymer, the negative charge on the surface of the MXene particles and the -C(=O)O of the anionic polymer in a liquid medium are not easily agglomerated. - The agglomeration effect of PVA is stronger than the effect of electrostatic repulsion between the MXene particles, and as a result, agglomeration between the MXene particles cannot be effectively prevented, and the MXene particles may not be dispersed well.
[0078] By using such a liquid composition with good dispersibility of MXene particles, the MXene particles can be densely present in the finally obtained composite material (composite material structure in this manufacturing example, the same applies below). In a liquid composition with good dispersibility of MXene particles, it is considered that the MXene particles are uniformly dispersed in the liquid medium. In the precursor structure formed using such a liquid composition, the MXene particles are also uniformly dispersed in the liquid medium, and the MXene particles can be present in a highly oriented state in the composite material after drying. When a composite material structure is formed on a substrate as in this manufacturing example, the MXene particles can be aligned and arranged so that the two-dimensional sheet surface of the MXene particles is approximately parallel (for example, within ±20°) to the surface of the substrate. As a result, a composite material with a high density of MXene particles can be obtained. A composite material with a high density of MXene particles is less susceptible to the influence of the surrounding environment, and therefore the environmental resistance can be improved (compared to conventional composite materials). For example, in high humidity conditions, a composite material with a higher density of MXene particles is less permeable to water molecules (fewer paths for water molecules to penetrate), and therefore can have improved moisture resistance.
[0079] In contrast, in a liquid composition in which the dispersibility of MXene particles is poor, unlike the present embodiment, it is believed that the MXene particles are unevenly distributed in the liquid medium and are partially present in an aggregated state. In a precursor structure formed using such a liquid composition, the MXene particles are also unevenly distributed in the liquid medium and are partially present in an aggregated state, and the aggregated MXene particles get in the way during drying (film formation), disturbing the orientation of the MXene particles. As a result, voids are generated near the aggregated MXene particles, resulting in a composite material with a low density of MXene particles. A composite material with a low density of MXene particles is easily affected by the surrounding environment, and therefore the environmental resistance is reduced (as in conventional composite materials). For example, in a high humidity condition, a composite material with a lower density of MXene particles is more susceptible to the intrusion of water molecules (there are more paths for water molecules to intrude), and therefore the moisture resistance is reduced.
[0080] As can be seen from the above, in this embodiment, by using a liquid composition that has good dispersibility of MXene particles, a composite material (a composite material structure in this manufacturing example) with a high density of MXene particles can be obtained, and therefore the environmental resistance (particularly moisture resistance) can be improved compared to conventional composite materials, and preferably environmental resistance (particularly moisture resistance) equivalent to that of a single MXene material (consisting essentially of only MXene particles and not including resin material) can be achieved.
[0081] Furthermore, although not essential to this embodiment, the anionic resin material is preferably a self-crosslinking resin material. This can further improve the environmental resistance (particularly the moisture resistance). Although the present disclosure is not bound by any theory, the reason is considered to be as follows.
[0082] A self-crosslinking resin material may be one in which a self-crosslinking functional group and / or a reactive functional group (which can react with a crosslinking agent) is introduced into an anionic polymer. The MXene particles may have a hydroxyl group or the like as a modification or terminal T, and such modification or terminal T may undergo a crosslinking reaction with the self-crosslinking and / or reactive functional group of the anionic polymer. When an anionic polymer crosslinked with an MXene particle is further crosslinked with another MXene particle, the anionic polymer is crosslinked between a plurality of MXene particles. The MXene particles crosslinked in this way are chemically bonded to each other and are less susceptible to the influence of the surrounding environment, thereby further improving the environmental resistance. For example, in high humidity conditions, the gaps between the MXene particles are less likely to be opened by water molecules, thereby further improving the humidity resistance.
[0083] The environmental resistance can be determined based on the rate of change over time of the physical properties of the composite material in a specific environment, and the smaller the rate of change, the higher the environmental resistance (particularly the moisture resistance). More specifically, the moisture resistance can be determined based on the rate of change over time of the physical properties of the composite material in a high humidity environment (e.g., 85% relative humidity), particularly in a high temperature and high humidity environment (e.g., 60°C temperature and 85% relative humidity), and the smaller the rate of change, the higher the moisture resistance. The physical properties of the composite material can be electrical properties, typically electrical conductivity. In other words, according to this embodiment, the rate of decrease over time of the electrical conductivity of the finally obtained composite material (the composite material structure in this manufacturing example) can be improved (compared to conventional composite materials).
[0084] In the final composite material (composite material structure in this manufacturing example), the ratio of the solid content of the anionic resin material to the total solid content of the MXene particles and the anionic resin material can be 0.1% by mass or more and 99.9% by mass or less, similar to the ratio in the liquid composition. When a conductive composite material is required, the ratio of the MXene particles to the total solid content of the MXene particles and the anionic resin material can be, for example, 50% by mass or more and 99.9% by mass or less, depending on the anionic resin material used.
[0085] In addition, according to this embodiment, it is possible to obtain a higher adhesion between the composite structure and the substrate than in the case of a film made of a single MXene material. A film made of a single MXene material easily coagulates and peels off with tape peeling (based on the cross-cut method defined in JIS K5600-5-6). In contrast, this embodiment uses a composite material containing MXene particles and an anionic resin material, which prevents coagulation and peeling and ensures film strength and adhesion.
[0086] The composite material (structure, for example, film) of the present embodiment may be used in any suitable application, such as an electrode or electromagnetic shield (EMI shield) in any suitable electric device, where maintaining high electrical conductivity (reducing the decrease in initial electrical conductivity) is required.
[0087] The electrodes are not particularly limited, and may be, for example, electrodes for capacitors, electrodes for batteries, bioelectrodes, electrodes for sensors, electrodes for antennas, etc. By using the composite material (structure, for example, a membrane) of the present embodiment, it is possible to obtain a large-capacity capacitor and battery, a low-impedance bioelectrode, and a highly sensitive sensor and antenna even in a smaller volume (volume occupied by the device).
[0088] The capacitor may be an electrochemical capacitor. The electrochemical capacitor is a capacitor that utilizes a capacity generated due to a physicochemical reaction between an electrode (electrode active material) and an ion (electrolyte ion) in an electrolyte, and can be used as a device that stores electric energy (electricity storage device). The battery may be a chemical battery that can be repeatedly charged and discharged. The battery may be, for example, a lithium ion battery, a magnesium ion battery, a lithium sulfur battery, a sodium ion battery, or the like, but is not limited thereto.
[0089] The bioelectrode is an electrode for acquiring a biosignal. The bioelectrode may be, for example, an electrode for measuring EEG (electroencephalogram), ECG (electrocardiogram), EMG (electromyogram), or EIT (electrical impedance tomography), but is not limited thereto.
[0090] The sensor electrode is an electrode for detecting a target substance, state, abnormality, etc. The sensor may be, for example, a gas sensor, a biosensor (a chemical sensor that utilizes a molecular recognition mechanism of biological origin), etc., but is not limited to these.
[0091] The antenna electrode is an electrode for emitting electromagnetic waves into space and / or receiving electromagnetic waves in space.
[0092] In particular, by using the composite material (structure, for example, film) of this embodiment, an electromagnetic shield with a high shielding rate (EMI shielding property) can be obtained.
[0093] Although the composite material and the manufacturing method of the composite material structure in one embodiment of the present disclosure have been described in detail above, various modifications of the present disclosure are possible. Note that the composite material of the present disclosure may be manufactured by a method different from the manufacturing method in the above-mentioned embodiment. EXAMPLES
[0094] Example 1 Preparation of MAX particles (precursor of MXene particles) TiC powder, Ti powder, and Al powder (all manufactured by Kojundo Chemical Laboratory Co., Ltd.) were mixed in a molar ratio of 2:1:1 for 24 hours in a ball mill containing zirconia balls. The mixed powder was sintered for 2 hours at 1350°C in an Ar atmosphere. The sintered body (block) was pulverized with an end mill to a maximum dimension of 40μm or less. Ti3AlC2 particles were obtained as MAX particles.
[0095] Etching of precursors (ACID method) Using the Ti3AlC2 particles (powder) prepared by the above method, etching was carried out under the following etching conditions to obtain a solid-liquid mixture (slurry) containing solid components derived from the Ti3AlC2 powder. (Etching conditions) Precursor: Ti3AlC2 (passed through a 45μm sieve) Etching solution composition: 49% HF 6mL H2O 18mL HCl (12M) 36mL Precursor input: 3.0g Etching container: 100mL Eyeboy Etching temperature: 35℃ Etching time: 24h Stirrer speed: 400 rpm
[0096] Post-etch cleaning The above slurry was divided into two, each of which was placed in two 50 mL centrifuge tubes. The slurry was centrifuged at 3500 G using a centrifuge, and the supernatant was discarded. 40 mL of pure water was added to the remaining precipitate in each centrifuge tube, and the tube was centrifuged again at 3500 G to separate and remove the supernatant. This operation was repeated 11 times. After the final centrifugation, the supernatant was discarded, and the Ti3C2T x - Moisture medium clay was obtained.
[0097] Lithium intercalation Ti3C2T prepared by the above method x -Li intercalation was carried out on the water medium clay by using LiCl as the Li-containing compound and stirring for 12 hours at 20°C to 25°C under the following conditions. (Li intercalation conditions) · Ti3C2T x - Moisture medium clay (MXene after washing): 0.75g solids LiCl: 0.75g Intercalation vessel: 100mL Eye Boy ·Temperature: 20℃ or higher and 25℃ or lower (room temperature) ·Time: 10h Stirrer speed: 800 rpm
[0098] Delamination The above Ti3C2T x (i) 40 mL of pure water was added to the aqueous medium clay, which was then stirred in a shaker for 15 minutes, (ii) centrifuged at 3500G, and (iii) the supernatant was collected as a single-layer MXene-containing solution. These steps (i) to (iii) were repeated a total of four times to obtain a single-layer MXene-containing supernatant. This supernatant was then centrifuged in a centrifuge at 4300G for two hours, after which the supernatant was discarded, and single-layer and single-layer MXene-containing clay was obtained as a single-layer and single-layer MXene-containing sample.
[0099] Preparation of MXene-water dispersion An MXene-water dispersion (MXene slurry) with a solid concentration (MXene particle concentration) of 34 mg / mL was prepared by mixing appropriate amounts of this MXene-containing clay and pure water.
[0100] -Membrane (composite membrane) formation 0.069 g of an anionic acrylic resin material (Aron (registered trademark) NW-400, manufactured by Toagosei Co., Ltd.) was placed in a 50 mL centrifuge tube as a resin material, and then 22.284 g of pure water was added to dilute the resin material. 17.647 g of the MXene-water dispersion (MXene particles: solid concentration 34 mg / mL) prepared as described above was added to the diluted resin material to make a total amount of 40.00 g. Then, the mixture was shaken and stirred for 15 minutes using an automatic shaker (SK550 1.1, manufactured by FAST & Fluid Co., Ltd.) to prepare a liquid composition containing MXene particles and the resin material. No aggregation of the MXene particles was observed in this liquid composition.
[0101] The obtained liquid composition was sprayed using a spray coater onto a 3 cm square glass substrate (Tempax, manufactured by SCHOTT) whose surface had been previously cleaned with oxygen plasma, to form a precursor film made of the liquid composition. After spraying, the substrate was dried with hot air. The above spraying and drying were repeated a total of 20 times. The precursor film was then dried in a normal pressure oven at 80°C for 2 hours and then in a vacuum oven at 150°C for about 15 hours to obtain a composite material film (spray method).
[0102] The mass ratio of the MXene particles to the solid content of the resin material in the composite material film can be considered to be 95% by mass:5% by mass, based on the composition of the liquid composition used.
[0103] Comparative Example 1 - Formation of film (MXene single material film) An MXene-water dispersion (MXene particles: solids concentration 34 mg / mL) was prepared in the same manner as in Example 1.
[0104] 22.353 g of pure water was added to a 50 mL centrifuge tube, and 17.647 g of the MXene-water dispersion (MXene particles: solid concentration 34 mg / mL) prepared as described above was added thereto for a total amount of 40.00 g. The mixture was then shaken and stirred for 15 minutes using an automatic shaker (SK550 1.1, manufactured by FAST & Fluid) to prepare a liquid composition containing MXene particles but not containing a resin material.
[0105] A film of the simple MXene material was obtained in the same manner as in Example 1, except that the obtained liquid composition was used.
[0106] Comparative Example 2 -Membrane (composite membrane) formation An MXene-water dispersion (MXene particles: solids concentration 34 mg / mL) was prepared in the same manner as in Example 1.
[0107] 0.108 g of an anionic polyurethane resin material (Rezamin D-4090, manufactured by Dainichi Seika Chemicals Co., Ltd.) was placed in a 50 mL centrifuge tube as a resin material, and then 22.245 g of pure water was added to dilute the resin material. 17.647 g of the MXene-water dispersion (MXene particles: solid concentration 34 mg / mL) prepared as described above was added to the diluted resin material to make a total amount of 40.00 g. Then, the mixture was shaken and stirred for 15 minutes using an automatic shaker (SK550 1.1, manufactured by FAST & Fluid Co., Ltd.) to prepare a liquid composition containing MXene particles and the resin material.
[0108] Except for using the obtained liquid composition, a composite material film was obtained in the same manner as in Example 1. Although the MXene particles were slightly aggregated in the liquid composition obtained above, a film could be formed.
[0109] The mass ratio of the MXene particles to the solid content of the resin material in the composite material film can be considered to be 95% by mass:5% by mass, based on the composition of the liquid composition used.
[0110] Example 2 Preparation of MAX particles (precursor of MXene particles) MAX particles were obtained in the same manner as in Example 1.
[0111] Precursor etching (MILD method) and Li intercalation Using the Ti3AlC2 particles (powder) prepared by the above method, etching and Li intercalation were carried out under the following etching conditions to obtain a solid-liquid mixture (slurry) containing solid components derived from the Ti3AlC2 powder. (Precursor etching and Li intercalation conditions) Precursor: Ti3AlC2 (passed through a 45μm sieve) Etching solution composition: LiF 3g HCl (9M) 30mL Precursor input: 3g Etching container: 100mL Eyeboy Etching temperature: 35℃ Etching time: 24h Stirrer speed: 400 rpm
[0112] Post-etch cleaning The above slurry was divided into two portions and placed in two 50 mL centrifuge tubes, and centrifuged at 3500 G using a centrifuge, after which the supernatant was discarded. (i) 40 mL of pure water was added to the remaining precipitate in each centrifuge tube, (ii) centrifuged again at 3500 G, and (iii) the supernatant was separated and removed. These steps (i) to (iii) were repeated a total of 10 times, and after confirming that the pH of the 10th supernatant was greater than 5, the supernatant was discarded, and Ti3C2T x - Moisture medium clay was obtained.
[0113] Delamination The above Ti3C2T x(i) 40 mL of pure water was added to the aqueous medium clay, which was then stirred in a shaker for 15 minutes, (ii) centrifuged at 3500G, and (iii) the supernatant was collected as a single-layer MXene-containing solution. These steps (i) to (iii) were repeated a total of four times to obtain a single-layer MXene-containing supernatant. This supernatant was then centrifuged in a centrifuge at 4300G for two hours, after which the supernatant was discarded, and single-layer and single-layer MXene-containing clay was obtained as a single-layer and single-layer MXene-containing sample.
[0114] Preparation of MXene-water dispersion An MXene-water dispersion (MXene slurry) with a solid concentration (MXene particle concentration) of 84 mg / mL was prepared by mixing appropriate amounts of this MXene-containing clay and pure water.
[0115] -Membrane (composite membrane) formation 0.069 g of an anionic acrylic resin material (Aron (registered trademark) NW-400, manufactured by Toagosei Co., Ltd.) was placed in a 50 mL centrifuge tube as a resin material, and then 32.165 g of pure water was added to dilute the resin material. 7.143 g of the MXene-water dispersion (MXene particles: solid content concentration 84 mg / mL) prepared as described above was added to the diluted resin material to make a total amount of 40.00 g. Then, the mixture was shaken and stirred for 15 minutes using an automatic shaker (SK550 1.1, manufactured by FAST & Fluid Co., Ltd.) to prepare a liquid composition containing MXene particles and the resin material.
[0116] A composite material membrane was obtained in the same manner as in Example 1, except that the obtained liquid composition was used.
[0117] The mass ratio of the MXene particles to the solid content of the resin material in the composite material film can be considered to be 95% by mass:5% by mass, based on the composition of the liquid composition used.
[0118] Comparative Example 3 - Formation of film (MXene single material film) An MXene-water dispersion (MXene particles: solids concentration 84 mg / mL) was prepared in the same manner as in Example 2.
[0119] 31.76 g of pure water was added to a 50 mL centrifuge tube, and 7.14 g of the MXene-water dispersion (MXene particles: solid concentration 84 mg / mL) prepared as described above was added thereto to make a total amount of 40.00 g. The mixture was then shaken and stirred for 15 minutes using an automatic shaker (SK550 1.1, manufactured by FAST & Fluid) to prepare a liquid composition containing MXene particles but not containing a resin material.
[0120] A film of the simple MXene material was obtained in the same manner as in Example 1, except that the obtained liquid composition was used.
[0121] Comparative Example 4 -Membrane (composite membrane) formation An MXene-water dispersion (MXene particles: solids concentration 84 mg / mL) was prepared in the same manner as in Example 2.
[0122] 0.108 g of an anionic polyurethane resin material (Rezamin D-4090, manufactured by Dainichi Seika Chemicals Co., Ltd.) was placed in a 50 mL centrifuge tube as a resin material, and then 31.775 g of pure water was added to dilute the resin material. 7.143 g of the MXene-water dispersion (MXene particles: solid concentration 84 mg / mL) prepared as described above was added to the diluted resin material to make a total amount of 40.00 g. Then, the mixture was shaken and stirred for 15 minutes using an automatic shaker (SK550 1.1, manufactured by FAST&Fluid Co., Ltd.) to prepare a liquid composition containing MXene particles and the resin material.
[0123] A composite material membrane was obtained in the same manner as in Example 1, except that the obtained liquid composition was used.
[0124] The mass ratio of the MXene particles to the solid content of the resin material in the composite material film can be considered to be 95% by mass:5% by mass, based on the composition of the liquid composition used.
[0125] Example 3 -Membrane (composite membrane) formation A liquid composition containing MXene particles and a resin material was prepared in the same manner as in Example 1.
[0126] The obtained liquid composition was suction filtered overnight using a Nutsche filter. A membrane filter (Durapore, pore size 0.45 μm, manufactured by Merck Ltd.) was used as the filter for suction filtration. After suction filtration, the precursor film on the filter was dried overnight at 80° C. in a vacuum oven to obtain a composite material film.
[0127] The mass ratio of the MXene particles to the solid content of the resin material in the composite material film was the same as in Example 1, based on the composition of the liquid composition used.
[0128] Comparative Example 5 - Formation of film (MXene single material film) A liquid composition containing MXene particles but not containing a resin material was prepared in the same manner as in Comparative Example 1.
[0129] A film of the simple MXene material was obtained in the same manner as in Example 3, except that the obtained liquid composition was used.
[0130] Comparative Example 6 -Membrane (composite membrane) formation A liquid composition containing MXene particles and a resin material was prepared in the same manner as in Comparative Example 2.
[0131] A composite material membrane was obtained in the same manner as in Example 3, except that the obtained liquid composition was used.
[0132] The mass ratio of the MXene particles to the solid content of the resin material in the composite material film was the same as in Comparative Example 2, based on the composition of the liquid composition used.
[0133] Comparative Example 7 An MXene-water dispersion (MXene particles: solids concentration 34 mg / mL) was prepared in the same manner as in Example 1.
[0134] 0.099 g of a PVA-containing resin material (Aron (registered trademark) AS-2000, manufactured by Toagosei Co., Ltd.) was placed in a 50 mL centrifuge tube as a resin material, and then 22.254 g of pure water was added to dilute the resin material. 17.647 g of the MXene-water dispersion (MXene particles: solid content concentration 34 mg / mL) prepared as described above was added to the diluted resin material to make a total amount of 40.00 g. The mixture was then shaken and stirred for 15 minutes using an automatic shaker (SK550 1.1, manufactured by FAST & Fluid Co., Ltd.) to prepare a liquid composition containing MXene particles and the resin material.
[0135] In the obtained liquid composition, the MXene particles aggregated and could not form a film.
[0136] Comparative Example 8 An MXene-water dispersion (MXene particles: solids concentration 84 mg / mL) was prepared in the same manner as in Example 2.
[0137] 0.099 g of a PVA-containing resin material (Aron (registered trademark) AS-2000, manufactured by Toagosei Co., Ltd.) was placed in a 50 mL centrifuge tube as a resin material, and then 32.758 g of pure water was added to dilute the resin material. 7.142 g of the MXene-water dispersion (MXene particles: solid content concentration 84 mg / mL) prepared as described above was added to the diluted resin material to make a total amount of 40.00 g. Then, the mixture was shaken and stirred for 15 minutes using an automatic shaker (SK550 1.1, manufactured by FAST & Fluid Co., Ltd.) to prepare a liquid composition containing MXene particles and the resin material.
[0138] In the obtained liquid composition, the MXene particles aggregated and could not form a film.
[0139] Table 1 summarizes the methods for producing the MXene particles, the type or presence of resin material, and the film-forming method in the above Examples 1 to 3 and Comparative Examples 1 to 8.
[0140] [Table 1] ARON NW-400: An anionic resin material (self-crosslinking type) that contains an anionic acrylic polymer that has at least one of a carboxylic acid group and a carboxylic acid salt group, and does not have an NH group, and contains tetraethylene glycol as a surfactant, but does not contain PVA. Resamine D-4090: Anionic resin material containing polyurethane polymer Aron AS-2000: A resin material (non-reactive type) containing an anionic acrylic (acrylic acid) polymer and PVA.
[0141] For Examples 1 to 3 and Comparative Examples 1 to 6 where a film was successfully formed (composite material films in Examples 1 to 3 and Comparative Examples 2, 4, and 6, and MXene single material films in Comparative Examples 1, 3, and 5), the moisture resistance of the films was evaluated as follows. Furthermore, for Examples 1 to 2 and Comparative Examples 1 to 4, the adhesion to the base material (glass substrate) was evaluated as follows. Note that in Example 3 and Comparative Examples 5 and 6, the films were prepared on a membrane filter by suction filtration, and since the membrane filter could be removed and only the film (self-standing film) could be used, adhesion was not evaluated.
[0142] (evaluation) Moisture resistance (high temperature and humidity test) The films (samples) prepared on the substrate in each of Examples 1 to 3 and Comparative Examples 1 to 6 were stored in a thermo-hygrostat at a temperature of 60° C. and a relative humidity of 85% after preparation, and the conductivity (S / cm) of the conductive film was measured one day after the start of storage and for an appropriate number of days thereafter. More specifically, the conductivity was measured by measuring the resistivity (surface resistivity) (Ω) at three points per sample, calculating the conductivity (S / cm) from the measured resistivity and the thickness (μm) of the film measured in advance, and adopting the arithmetic average value of the conductivity at the three points thus obtained. A low resistivity meter (Loresta AX MCP-T370, manufactured by Mitsubishi Chemical Analytical Co., Ltd.) was used to measure the resistivity. A stylus-type surface profiler (DEKTAK8, manufactured by Bruker Japan Co., Ltd.) was used to measure the thickness, and the thickness (μm) of the film was measured immediately before being placed in the thermo-hygrostat, and this measured value was used to calculate the conductivity.
[0143] The conductivity just before (initial) placing in the thermo-hygrostat was set to 100%, and the rate of change in conductivity was calculated. The results are shown in Figures 3 to 5. The conductivity just before (initial) placing in the thermo-hygrostat and the conductivity after one day were as shown in Table 2.
[0144] [Table 2]
[0145] In the evaluation of electrical conductivity, Comparative Examples 1, 3 and 5, which do not contain a resin material, are understood as controls.
[0146] With reference to Table 1 and FIG. 3, in Example 1 and Comparative Examples 1 and 2, a film was formed by spraying using MXene particles produced by the ACID method. The conductivity was measured initially and after 1 day, as well as after 7 and 14 days, to examine the rate of change in conductivity. In Comparative Example 1 (control), the rate of change in conductivity after 14 days was -50%. It is considered that the MXene particles themselves have hydroxyl groups, and Li intercalated into the MXene particles attracts water molecules, resulting in the absorption of water and the decrease in conductivity. In Example 1, the rate of change in conductivity after 14 days was -54%. The degree of decrease in Example 1 was equivalent to that of Comparative Example 1. In contrast, in Comparative Example 2, the rate of change in conductivity after 14 days was -67%. The degree of decrease in Comparative Example 2 was significantly greater than the degrees of decrease in Comparative Example 1 and Example 1.
[0147] With reference to Table 1 and FIG. 4, in Example 2 and Comparative Examples 3 and 4, films were formed by spraying using MXene particles produced by the MILD method. The conductivity was measured initially and after one day, as well as after three days, to examine the rate of change in conductivity. In Comparative Example 3 (control), the rate of change in conductivity was -36% after one day and -69% after three days. In Example 2, the rate of change in conductivity was -44% after one day and -67% after three days. The extent of decrease in Example 2 was equivalent to that of Comparative Example 3. In contrast, in Comparative Example 4, the rate of change in conductivity was -59% after one day and -71% after three days. The extent of decrease in Comparative Example 4 was significantly larger than the extent of decrease in Comparative Example 3 and Example 2, especially after one day.
[0148] Comparing Example 1 (ACID method) in FIG. 3 with Example 2 (MILD method) in FIG. 4, it is understood that using MXene particles produced by the ACID method is more preferable than using MXene particles produced by the MILD method because higher moisture resistance can be obtained. This is because MXene particles produced by the ACID method have lower moisture absorption than MXene particles produced by the MILD method, and it is believed that the effect of using the anionic resin material in the present disclosure is more likely to be achieved. It is believed that moisture absorption by MXene particles occurs when water molecules are attracted to the hydroxyl groups on the surface of the MXene particles and the intercalated Li. It is presumed that the surface functional groups and the amount of Li of the MXene particles differ depending on the etching method (ACID method or MILD method). Therefore, it is believed that the surface functional groups and the amount of Li differ between MXene particles produced by the ACID method and MXene particles produced by the MILD method, and therefore the moisture absorption also differs.
[0149] With reference to Table 1 and FIG. 5, in Example 3 and Comparative Examples 5 and 6, a membrane was formed by suction filtration using MXene particles produced by the ACID method. The conductivity was measured initially and after one day, as well as after two days, to examine the rate of change in conductivity. In Comparative Example 5 (control), the rate of change in conductivity was -50% after one day and -55% after two days. In Example 2, the rate of change in conductivity was -46% after one day and -56% after two days. The extent of decrease in Example 3 was equivalent to that of Comparative Example 5. In contrast, in Comparative Example 6, the rate of change in conductivity was -61% after one day and -61% after two days. The extent of decrease in Comparative Example 6 was significantly larger than the extent of decrease in Comparative Example 5 and Example 3, especially after one day.
[0150] Comparing Example 1 (spray) in Fig. 3 with Example 3 (suction filtration) in Fig. 5, it is understood that the film formed by spraying is preferable to the film formed by suction filtration because it has higher moisture resistance. This is thought to be because the film formed by spraying has a higher density (fewer voids) than the film formed by suction filtration, and the effect of using the anionic resin material in this disclosure is more likely to be exhibited. On the other hand, the film formed by suction filtration is thought to be more likely to have a sparse structure.
[0151] Adhesion (tape peel test) The adhesion (bonding strength) of the films (samples not subjected to moisture resistance evaluation) formed on the substrate (glass substrate) in each of Examples 1 and 2 and Comparative Examples 1 to 4 to the substrate was evaluated in accordance with the cross-cut method defined in JIS K5600-5-6. The evaluation results are classified as follows. The results are shown in Table 3. 0: The edges of the cut are completely smooth and there are no peeling marks on any of the grids. 1: Small separations of the coating at the intersections of cuts. The cross-cut area affected is not significantly more than 5%. 2: The coating has delaminated along the edges of cuts and / or at intersections. Clearly more than 5% but not more than 15% of the cross-cut area is affected. 3: The coating has partially or completely spalled along the edges of the cuts and / or has partially or completely spalled various areas of the mesh. Cross-cut areas are clearly more than 15% but not more than 35% affected. 4: The coating has partially or completely peeled off significantly along the edges of the cuts and / or partially or completely peeled off in several sections. Cross-cut areas not appreciably more than 65% affected. 5: Any degree of peeling that cannot be classified as category 4.
[0152] [Table 3]
[0153] Referring to Table 3, of Example 1 and Comparative Examples 1-2 in which films were formed by spraying using MXene particles produced by the ACID method, the films of Example 1 and Comparative Example 2 were evaluated as 0, a lower evaluation value than the evaluation of 4 for the film of Comparative Example 1. In Example 1 and Comparative Example 2, a composite material film containing MXene particles and a resin material was formed, and it is believed that adhesion was ensured by mixing in the resin material. In contrast, in Comparative Example 1, a film of a single MXene material was formed, and no resin material was mixed in, so it is believed that adhesion could not be ensured.
[0154] Of Example 2 and Comparative Examples 3-4, in which films were formed by spraying using MXene particles produced by the MILD method, the films of Example 2 and Comparative Example 4 were rated 3 and 4, respectively, which were lower evaluation values than the evaluation of 5 for the film of Comparative Example 3. In Example 2 and Comparative Example 4, a composite material film containing MXene particles and a resin material was formed, and it is believed that by mixing in the resin material, adhesion was improved compared to Comparative Example 4, in which no resin material was mixed in.
[0155] Comparing Example 1 (ACID method) and Example 2 (MILD method), it is understood that using MXene particles produced by the ACID method is more preferable than using MXene particles produced by the MILD method because higher adhesion can be obtained. As described above, the MXene particles produced by the ACID method and the MXene particles produced by the MILD method have different surface functional groups and amounts of Li, and it is considered that the adhesion is also different accordingly. [Industrial Applicability]
[0156] The composite material of the present disclosure may be utilized in any suitable application, and may be preferably used, for example, as an electrode or electromagnetic shield in an electrical device. [Explanation of symbols]
[0157] 1a, 1b layer body (M m X n layer) 3a, 5a, 3b, 5b Modified or terminal T 7a, 7b MXene layers 10, 10a, 10b MXene particles (particles of two-dimensional materials) 11 Anionic resin materials 20 Composite materials (composite material structures)
Claims
1. 1. A composite material comprising particles of a two-dimensional material comprising one or more layers and a resin material, The layer has the following formula: M m X n wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 or more and 4 or less, m is greater than n and is equal to or less than 5. and a modification or terminal T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, the resin material is an anionic resin material containing an anionic polymer having at least one of a carboxylic acid group and a carboxylate salt group and having no NH group (excluding a resin material containing polyvinyl alcohol); A composite material, wherein the ratio of the particles of the two-dimensional material to the total of the particles of the two-dimensional material and the solid content of the resin material is 50% by mass or more and 99.9% by mass or less.
2. The composite material of claim 1 having the form of a structure.
3. The composite material of claim 2 , wherein the structure is a membrane.
4. The composite material according to claim 1 , wherein the resin material is an acrylic resin material.
5. A composite material comprising particles of a two-dimensional material having one or more layers and a resin material, The layer has the following formula: M m X n wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 or more and 4 or less, m is greater than n and is equal to or less than 5. and a modification or terminal T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, the resin material is an anionic resin material containing an anionic polymer having at least one of a carboxylic acid group and a carboxylate salt group and having no NH group (excluding a resin material containing polyvinyl alcohol); A composite material, wherein the resin material is a self-crosslinking resin material.
6. Said M m X n But Ti 3 C 2 The composite material according to any one of claims 1 to 5,
7. 1. A method for manufacturing a composite material structure, comprising the steps of: (a) preparing a liquid composition comprising particles of a two-dimensional material comprising one or more layers, a resin material, and a liquid medium, The layer has the following formula: M m X n wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 or more and 4 or less, m is greater than n and is equal to or less than 5. and a modification or terminal T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, The resin material is an anionic resin material containing an anionic polymer having at least one of a carboxylic acid group and a carboxylate salt group and having no NH group (excluding resin materials containing polyvinyl alcohol); and (b) forming a precursor structure on a substrate using the liquid composition and at least drying the precursor structure to obtain a composite material structure; A manufacturing method, in which a ratio of the particles of the two-dimensional material to a total of the particles of the two-dimensional material and the solid content of the resin material is 50 mass % or more and 99.9 mass % or less.
8. The method of claim 7 , wherein the composite structure is a composite membrane.
9. The method for producing a composite material structure according to claim 7 , wherein the resin material is an acrylic resin material.
10. A method for producing a composite material structure, comprising the steps of: (a) preparing a liquid composition comprising particles of a two-dimensional material comprising one or more layers, a resin material, and a liquid medium, The layer has the following formula: M m X n wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 or more and 4 or less, m is greater than n and is equal to or less than 5. and a modification or terminal T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, The resin material is an anionic resin material containing an anionic polymer having at least one of a carboxylic acid group and a carboxylate salt group and having no NH group (excluding resin materials containing polyvinyl alcohol); and (b) forming a precursor structure on a substrate using the liquid composition, and at least drying the precursor structure to obtain a composite material structure; Including, 4. The method for producing a composite material structure, wherein in (a), the resin material is a self-crosslinking resin material.
11. 8. The method for producing a composite material structure according to claim 7, wherein in (a), a ratio of the solid content of the resin material in the liquid composition to a total of the particles of the two-dimensional material and the solid content of the resin material is 0.1 mass% or more and 99.9 mass% or less.
12. Before the step (a), The formula: M m AX n (In the formula, M, X, n, and m are as defined above, A is at least one Group 12, 13, 14, 15, or 16 element. and obtaining particles of the two-dimensional material by a method comprising the steps of: etching a raw material represented by the formula: with an etching solution containing hydrofluoric acid. The method of claim 7 further comprising:
13. Before the step (a), The formula: M m AX n (In the formula, M, X, n, and m are as defined above, A is at least one Group 12, 13, 14, 15, or 16 element. The method of obtaining particles of the two-dimensional material includes etching a raw material represented by the formula: with an etching solution containing a fluoride and an acid (except for hydrofluoric acid). The method of claim 7 further comprising:
14. The method for producing a composite material structure according to claim 7 , wherein in (b), the precursor structure is formed by spraying the liquid composition onto the substrate.
15. Said M m X n But Ti 3 C 2 The method for producing a composite material structure according to claim 7,
Citation Information
Patent Citations
Novel MXenes modified anticorrosive paint and preparation method thereof
CN108715725A
Preparation method and application of carbon-coated composite material
CN111276684A
Method for preparing titanium carbide (MXene) flexible electrode based on polymer high-temperature carbonization, and application thereof
CN111943208A
Self-repairing dielectric elastomer composite material and preparation method thereof
CN113088023A
Early-warning hydrogen sensor gas sensitive layer of lithium battery energy storage system and application of early-warning hydrogen sensor gas sensitive layer
CN116482184A